The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fimmu.2017.00610
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Double-Stranded DNA IgG Participates in Renal Fibrosis through Suppressing the Suppressor of Cytokine Signaling 1 Signals

Abstract: Suppressor of cytokine signaling 1 (SOCS1) participates in renal fibrosis by downregulating Janus kinase 2 (JAK2)/signal transducer and activator of transcription 1 (STAT1)-mediated cytokine signaling. Recently, it was found that anti-double-stranded DNA (dsDNA) IgG induces the synthesis of profibrotic cytokines by renal cells. To explore the potential effect of anti-dsDNA IgG on SOCS1-mediated renal fibrosis, kidney tissues were collected from patients with lupus nephritis (LN) as well as MRL/lpr lupus-prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Systemic lupus erythematosus is characterized by serum positivity of anti-dsDNA autoantibodies, which are produced by B cell-derived plasma cells ( 52 ). Anti-dsDNA autoantibodies are instrumental in LN through recognition of multiple self-antigens and initiation of renal fibrosis ( 53 55 ). BAFF, which is a DC- and monocyte-derived cytokine of TNF family, is crucial in regulating B cell maturation, survival, and function ( 56 ).…”
Section: Socs1 Participates In the Hematologic Abnormalities In Slementioning
confidence: 99%
See 4 more Smart Citations
“…Systemic lupus erythematosus is characterized by serum positivity of anti-dsDNA autoantibodies, which are produced by B cell-derived plasma cells ( 52 ). Anti-dsDNA autoantibodies are instrumental in LN through recognition of multiple self-antigens and initiation of renal fibrosis ( 53 55 ). BAFF, which is a DC- and monocyte-derived cytokine of TNF family, is crucial in regulating B cell maturation, survival, and function ( 56 ).…”
Section: Socs1 Participates In the Hematologic Abnormalities In Slementioning
confidence: 99%
“…In progressive LN, fibrosis is one of the main pathologies, and it contributes to the development of end-stage renal disease, which is evidenced by glomerular sclerosis ( 3 ). Wang et al have demonstrated that SOCS1 expression is decreased in the glomeruli of LN patients and in MRL/lpr mice with anti-dsDNA IgG deposition as compared with their control groups ( 53 ). In MRL/lpr mice, STAT1 is overexpressed in glomerular mesangial, endothelial, and tubular epithelial cells, whereas SOCS1 is downregulated accordingly ( 62 ).…”
Section: Socs1 Inhibition Is Pivotal In the Pathogenesis Of Lnmentioning
confidence: 99%
See 3 more Smart Citations